El financiamiento a las micro y pequeñas empresas del sector comercial de Guadalupe para contribuir a su crecimiento. - Javier Lopez, Rita Vanessa (2015)
This thesis after investigating the situation Trade MYPERS District of Guadalupe in regard to its formality and informality, origin of their own and other resources and their management of the financing required for working capital and fixed assets and problems of access to credit from banks and nonbanks as the extent of being able to qualify for credit subject proposes a strategic action plan given their diagnosis by SWOT matrix to generate better growth Trade MYPES of Guadalupe ; likewise determined at Country behavior Active Financing to promote development through financial intermediation as the Banks and Non-Banking. Financial Intermediation Indirect or Money Market appeared in favorable economic times, as the first choice to support entrepreneurs to boost their businesses and still continue their work of financial intermediation and form very competitive. An analysis of the microfinance sector and the role of competition and Commercial MYPES with social responsibility of both parties will allow for proper growth of the business and financial intermediation in the District of Guadalupe in La Libertad region. The research problem refers to the Proposal of Power Funding to contribute to the growth of Micro and Small Enterprises Retail Sector District of Guadalupe. It correlated with the Millennium: General and specific and population and sample applied in the commercial sector of MSEs of Guadalupe came from my research as a contribution to establish the status and diagnostics of MSEs: That the greatest obstacles to obtaining required financing by micro and small businesses translate into high rates of credit and transaction costs, and guarantees the documentation to be submitted even for small loan amounts The degree of formality and informality Trade MYPES of Guadalupe: 44% formal, semi casual and informal 37% 19% is a limiting factor in obtaining the necessary financing to grow their businesses.